Fancy nancy and the mermaid ballet ebook - O'Connor, Jane (Fancy Nancy., 2012)
*NOW A HIT TV SERIES ON DISNEY JUNIOR* From the dazzling bestselling duo Jane O'Connor and Robin Preiss Glasser comes a fancy, frilly ballet story with a lot of heart. Young ballerinas and Fancy Nancy fans will shout encore! Fancy Nancy is ready for the spotlight! Fancy Nancy and her best friend, Bree, couldn't be more excited about their upcoming dance show. After all, it's all about mermaids, and who knows how to be a fancy, glamorous mermaid better than Fancy Nancy herself? But when another ballerina wins the coveted role of the mermaid, Nancy is stuck playing a dreary, dull tree. Can Nancy bring fancy flair to her role, even though it isn't the one she wanted? And when disaster strikes right before the big ballet, who will step into the spotlight? Perfect for fans of the Eloise and Olivia books. Ooh la la! Fancy Nancy is starring in her own fabulous TV show on Disney Junior. READ THE BOOKS THAT STARTED IT ALL! Fancy Nancy Fancy Nancy and the Posh Puppy Fancy Nancy: Bonjour, Butterfly Fancy Nancy: Splendiferous Christmas Fancy Nancy and the Fabulous Fashion Boutique Fancy Nancy and the Mermaid Ballet Fancy Nancy: Fanciest Doll in the Universe Fancy Nancy and the Wedding of the Century Fancy Nancy 10th Anniversary Edition Fancy Nancy: Saturday Night Sleepover Fancy Nancy: Oodles of Kittens